Field reports form for submitting seasonal observations of Iowa birds, Carolyn Fischer, spring 1999 - Fischer, Carolyn J.et al (1999)
An annotated list of birds sighted by Carolyn Fischer. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1999. Epson - sheet feed